A 5 years’ experience of a parent-baby day unit: impact on baby’s development - Moureau, Audrey; Cordemans, Louise; Gregoire, Caroline; Benoît, Pirmez; Delvenne, Veronique (Frontiers in Psychiatry, 2023)
Introduction Psychiatric Mother-Baby Units are well established in France, United Kingdom, and Australia, mostly in full-time hospitalization. Inpatient units are considered as best practice for improving outcomes for mothers and babies when the mother is experiencing severe mental illness and many studies have showed the effectiveness of care for the mother or the mother-infant relationship. Only a limited number of studies have focused on the day care setting or on the development of the baby. Our parent-baby day unit is the first day care unit in child psychiatry in Belgium. It offers specialized evaluation and therapeutic interventions focused on the baby and involves parents with mild or moderate psychiatric symptoms. The advantages of day care unit is to reduce the rupture with social and family living. Aims The objective of this study is to evaluate the effectiveness of parent-baby day unit in prevention of babies’ developmental problems. First, we present the clinical characteristics of the population treated in the day-unit in comparison to the features presented in the literature review about mother-baby units, which usually receive full-time treatment. Then, we will identify the factors that might contribute to a positive evolution of the baby’s development. Materials and methods In this study, we retrospectively analyze data of patients admitted between 2015 and 2020 in the day unit. Upon admission, the 3 pillars of perinatal care – babies, parents, and dyadic relationships – have systematically been investigated. All the families have received a standard perinatal medico-psycho-social anamnesis, including data on the pregnancy period. In this unit, all the babies are assessed at entry and at discharge using the diagnostic 0 to 5 scale, a clinical withdrawal risk, and a developmental assessment (Bayley). Parental psychopathology is assessed with the DSM5 diagnostic scale and the Edinburgh scale for depression. Parent–child interactions are categorized according to Axis II of the 0 to 5 scale. We have evaluated the improvement of children symptomatology, the child development and the mother–child relation between the entrance (T1) and the discharge (T2) and we have compared two groups of clinical situations: a group of patients with a successful evolution (considering baby’s development and the alliance with the parents) and a group of unsuccessful evolution during hospitalization. Statistical analysis We use descriptive statistics to characterize our population. To compare the different groups of our cohort, we use the T-test and non-parametric tests for continue variables. For discrete variables, we used the Chi2 test of Pearson. Discussion The clinical population of the day unit is comparable to the mother-baby units in terms of psychosocial fragility but the psychopathological profile of the parents entering the day unit shows more anxiety disorder and less post-partum psychosis. The babies’ development quotient is in the average range at T1 and is maintained at T2. In the day unit, the number of symptoms as well as the relational withdrawal of the babies is reduced between T1 and T2. The quality of parent–child relationship is improved between T1 and T2. The children of the group of pejorative evolution had a lower developmental quotient at the T1 and an overrepresentation of traumatic life events. Conclusion These results indicate that parent-baby day unit lead to positive outcomes in clinical situations with anxio-depressive parents, relational withdrawal of the babies, functional problems of the babies but not when a significant impact on the development of the baby already exists. The results of this study can guide therapeutic approaches for the benefit of care in parent-baby day units, and improve the development of the child and of the dyadic relationships.